EFFECT OF MERGERS AND ACQUISITION ON COMPANY PERFORMANCE IN INDIA - Dhayfule, Jaynendra (2009)
In the past, numerous studies have been conducted in the past to analyse the effect of Mergers and Acquisition on the performance of the company. This paper aims to analyse the effect Mergers and Acquisitions have had on the performance of the Indian companies. In this study, the performance of a group of 1433 companies from the chemical industry of India were studied and analysed over a period of 20 years from 1988 to 2008 using the accounting information of these companies over the two decades. The obtained results confirmed that there is an effect of Mergers and acquisitions on the performance of a company. The results found that Sales of a firm and its income both increased following a merger. Also no cost reductions were observed following a merger as mentioned in different literatures.